Recent advances in the synthesis of gem-dimethylcyclobutane natural products. Issue 10 (11th March 2019) - Hancock, Erin N.; Wahl, Johannes M.; Brown, M. Kevin
Abstract : gem -Dimethylcyclobutanes are a common motif found in a multitude of natural products, and thus these structures have captivated synthetic chemists for years. Abstract : Covering: January 2000 to July 2018 gem -Dimethylcyclobutanes are a common motif found in a multitude of natural products, and thus these structures have captivated synthetic chemists for years. However, until the turn of the century, most synthetic efforts relied upon the use of widely available terpenes, such as pinene or caryophyllene, that already contain the gem -dimethylcyclobutane motif. This approach limits the scope of molecules that can be accessed readily. This review highlights recent syntheses in which the gem -dimethylcyclobutane is assembled via de novo approaches. An outlook on the future of this research area is also provided.